Exploring Cloud Computing Advancement and Future Technology Direction Impacts - Kumar Mutyala, Deeraj (International Journal of Computer Sciences and Engineering, 2024)
Cloud computing is a crucial element of contemporary computing structure, offering scalability, flexibility, and cost-effectiveness to organizations in various industries. This paper aims to thoroughly examine cloud computing, covering its evolution, key features, adoption trends, challenges, and future potential. Utilizing a mixed-methods approach, this study integrates literature reviews, case studies, surveys, and interviews to reveal valuable insights into how cloud computing is transforming businesses and society.